NILAI DEMOKRASI DALAM PEMBELAJARAN FIKIH DI MADRASAH TSANAWIYAH - Mazrur Mazrur (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Making democratic citizens is one of the functions of national education. For that we need to develop democratic value, by applying democratic value in learning activities. Fikih lesson is one of many religious subjects containing different views which has been taught in Madrasah Tsanawiyah (MTs). MTs student have already started thinking abstractly that make clash of views and experiences between students. This requires teachers applying democratic value in learning Fikih lesson. Research conducted at Madrasah Tsanawiyah Negeri 1 Palangka Raya and Madrasah Tsanawiyah Muslimat NU Palangka Raya have multicultural student. This research can be concluded that MTs Palangka Raya Fikih learning applied democratic value in learning activities such freedom, equality, tolerance, openness, trust and competition. Factors affecting democratic values application are students 'readiness, teachers ability to understand students' cognitive development, the creation of a pleasant atmosphere, freedom interaction and using humanistic by developing structural and cultural communication.